How to draw students’ attention - Salimova Bashorat Sadridinovna (Zien Journals, 2022)
One of the biggest challenges teachers face is getting and maintaining the attention of their students .Effective teaching requires this skill but it takes time and practice to learn.Whether you are just starting out or have been teaching for decades it is hard to keep students focused on task especially young learners get easily distracted and it can be challenging to come up with ways of keeping them engaged.Moreover young learners have relatively short attention spans .Since the students have various interests and levels of knowledge it is impossible to have the whole class fully –engaged in something for a long period of time , so it is highly recommended to work out a number of activities beforehand for per lesson as well
Keywords: recommended; challenges; getting; maintaining